A Question Answering System over Chronic Diseases and Epigenetics Knowledge - Almansa, Luciana; Rubio, Gabriel; Macedo, Alessandra (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2020)
Medical records describe patients’ health conditions and help experts to decide on treatments. The scientific biomedical knowledge can improve the prevention and treatment of diseases and promote innovation and discovery in health. However, healthcare professionals may have difficulty in searching for relevant scientific information due to lack time and constant literature update. The present work proposes a Question Answering (Q&A) architecture to support a more focused search for information about chronic diseases. A user question in natural language initiates the search for answering and promoting knowledge such as a learning healthcare system. To evaluate the system, we employ a reference collection on epigenetics and chronic disease and calculate performance measures like precision, recall and F-measure.